2021
DOI: 10.3390/nu14010081
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of Clinical Trial Protocols for Foods with Function Claims (FFC) in Japan: Consistency between Clinical Trial Registrations and Published Reports

Abstract: Background: A new type of foods with a health claims notification system, the Foods with Function Claims (FFC), was introduced in Japan in April 2015. This cross-sectional study sought to clarify compliance of clinical trial protocols reported as the scientific basis of efficacy in the FFC system. Methods: All articles based on clinical trials published on the Consumer Affairs Agency website from 1 July 2018 to 30 June 2021 were reviewed. Items assessed included first author characteristics (for-profit or acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…About 80% of RCT abstracts, full texts, and conclusions exhibited ''spin,'' similar to 73% in advertisements/press releases. This aligns with prior studies indicating widespread selective outcome reporting in Japanese FFCrelated RCTs [14,15]. Metaepidemiological studies conducted in various countries have highlighted the problem of selective outcome reporting in nutritional research [13,78,79].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…About 80% of RCT abstracts, full texts, and conclusions exhibited ''spin,'' similar to 73% in advertisements/press releases. This aligns with prior studies indicating widespread selective outcome reporting in Japanese FFCrelated RCTs [14,15]. Metaepidemiological studies conducted in various countries have highlighted the problem of selective outcome reporting in nutritional research [13,78,79].…”
Section: Discussionsupporting
confidence: 87%
“…that the Japanese Consumer Affairs Agency mandates the registration of dietary supplement trials in either the UMIN-CTR or the ICTRP [19], a search of these two databases should suffice to capture all relevant RCT registrations involving CROs in Japan, although 98% of the studies are registered in the UMIN-CTR [14].…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Ministry of Health, Labour and Welfare, Japan, the foods labeled "so-called health food" are not defined by law but refer to food that is widely sold or used as food contributing to health conservation and enhancement. 4) Among the "food with health claims," Food for Specified Health Use (FOSHU) and Food with Function Claims (FFC) are widely used for self-care/ prevention and health maintenance/enhancement practices, which may contribute to reducing the burden on limited medical resources [5][6][7][8][9][10][11][12] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…A 2021 study reported that compliance with the CT protocols in the FFC system was suboptimal in transparency. In addition to selective reporting, another problem was that the content of the intervention (test food) was intentionally concealed [5]. A subsequent 2022 study by these same researchers reported that randomization, deviations from the intended interventions, measurement of the outcomes, and selective reporting (particularly regarding the RoB, including a lack of ITT analysis, unknown compliance, and multiple outcome tests) seriously damaged the studies' quality [6].…”
Section: Introductionmentioning
confidence: 99%